Palms and Palm Use in Ambalabe, a Community in Eastern Madagascar. - Bussmann, Rainer W.; Paniagua Zambrana, Narel; Kuhlman, Alyse; Rakotoarivony, Fortunat; Razanatsima, Aina; Rakotoarivelo, Nivo; Razafitsalama, Jeremy Lalao; Randrianasolo, Armand; Randrianasolo, Armand (Ethnobotany Research and Applications, 2015)
Twenty-six native palm species of three genera were identified for Vohibe Forest, eastern Madagascar. In addition, two introduced (Cocos nucifera L., Elaeis guineensis Jacq.) and one native/possibly introduced species (Raphia farinifera (Gaertn.) Hyl.) are cultivated in the area. Local participants of an inventory on palm species and uses mentioned seven native species of two genera, including two folk species, but no plants could be found and no vouchers were collected. This makes Vohibe one of the richest palm hotspots in Madagascar. Palms play an important role in the life of the local population in Madagascar, providing food, material for utensils, medicine, and construction, but reports on palm use have been rare. Over 95% of the species are endemic to Madagascar. The use of palms is often destructive and possibly threatens some important species. In Vohibe Forest, nine local and three introduced species were used as resource by the population.